Process-property relationships of protonic ceramic electrolytes - Choi, Hyung Jong; Kim, Keun Hee; Jeong, Heon Jun; Kim, Dong Hwan; Han, Gwon Deok; Ji, Ho-Il; Lee, Jong-Ho; Prinz, Fritz B.; Bae, Kiho; Shim, Joon Hyung (Elsevier, 2025)
The effects of sintering temperature and Zr/Ce ratio on BaZrxCe0.8–xY0.1Yb0.1O3−δ (BZCYYb) for proton ceramic fuel cell applications were investigated. Higher sintering temperatures and higher Ce contents led to increased formation of Y/Yb-rich secondary phases, attributed to Ba evaporation and Ce loss, which disrupted B-site stability. Electrochemical testing using thin-film electrolytes on the anode-supported cells showed that sintering at ≥1400 °C caused high interfacial resistance due to these secondary phases. In contrast, sintering at 1300 °C resulted in insufficient densification and high ohmic resistance. The optimal performance was achieved with a BZCYYb 2611 sample sintered at 1350 °C, exhibiting good densification, minimal secondary phase formation, and high power density across various operating temperatures. This sample demonstrated the best chemical and electrochemical stability.